Treatment of palm oil effluent (POME) using membrane bioreactor. - Hazlan, Haris (2006)
Malaysia is the largest producer and exporter of palm oil. The serious problems in the palm fruit processing is the managing of the wastes generated during the rocesses. The wastes consist of a significant amount of solid wastes and a wastewater called palm oil mill effluent (POME). POME is a thick brownish liquid that contains high amount of total solids (40,500 mg/L), oil and grease (4000 mg/L), Chemical Oxygen Demand (50,000 mg/L), and Biochemical Oxygen Demand (25,000 mg/L). This highly polluting effluent is becoming a major problem to environment as if it not being treated well before discharged based on standard limit imposed by The Malaysian Department of Environment for effluent discharged. A POME treatment based on membrane technology, which is also an alternative treatment, shows highly potential to overcome the environment problem. Before membrane bioreactor pilot plant system is being introduced, a bioreactor in lab-scale is being set-up to determine the vital information regarding the most effective way to treat the wastewater. Samples from mixing ponds which act as activated sludge are collected and being analyze using water analyzer method to obtain parameters such as BOD, COD, suspended solid, turbidity and pH. Wastewater sample from facultative ponds is also being analyzed than mix with activated sludge treated in the bioreactor. Result from lab-scale bioreactor is used in membrane bioreactor pilot plant system to treat the wastewater. Result from bioreactor treatment in pilot plant scale show a decrement 61.2 % of BOD and 58.9% of COD, suspended solid and turbidity is also reducing up 35.3% and 20.4% with pH in range of 5-9. After the wastewater was treated in the ultrafiltration membrane system, high quality water with total of deterioration for all parameter is up to 99.9% and pH up to 7.39. This results show that the membrane bioreactor treatment system is highly effective in treating POME.